Karski how one man tried to stop the Holocaust - Wood, E. Thomas 1963-; Jankowski, Stanisław M. 1945- (Wiley, 1994)
A young Polish diplomat turned cavalry officer at the outbreak of World War II, Karski joined the Polish underground movement in 1939 after ingeniously escaping from a Soviet detention camp. Most of the Polish officers held with him were later executed. Karski became a courier for the underground crossing enemy lines to serve as liaison between occupied Poland and the free world. Captured by the Gestapo in 1940 he was savagely tortured
Keywords: Holocaust, Jewish (1939-1945) - Poland; Karski, Jan <1914->; Karski, Jan <1914-2000>; Karski, Jan -- 1914-2000; Poland - Ethnic relations; Poland - History - Occupation - 1939-1945; Geschichte; Geschichte 1939-1945; Guerre mondiale, 1939-1945 - Mouvements de résistance - Pologne - Biographies; Holocaust; Holocauste, 1939-1945 - Pologne; Jews - Poland - Persecutions; Juifs - Persécutions - Pologne - Histoire - 20e siècle; Tweede Wereldoorlog; World War - 1939-1945 - Undergraund movements - Poland - Biography; Juden; Judenvernichtung; Weltkrieg (1939-1945); Holocaust, Jewish (1939-1945) -- Poland; Jews -- Persecutions -- Poland; World War, 1939-1945 -- Underground movements -- Poland -- Biography; Information; Besetzung; Untergrundbewegung; Alliierte; Zweiter Weltkrieg; Pologne - Histoire - 1939-1945 (Occupation); Pologne - Relations interethniques; Polen; Poland -- Ethnic relations; Poland -- History -- Occupation, 1939-1945; Biografie -- 1939-1945; Quelle